Effective dosage and mode of exercise for enhancing cognitive function in Alzheimer's disease and dementia: a systematic review and Bayesian Model-Based Network Meta-analysis of RCTs - Yuan Yuan; Yong Yang; XiaoFei Hu; Lin Zhang; Zhiyu Xiong; Ying Bai; JiaLe Zeng; Feng Xu (BMC Geriatrics, 2024)
Abstract Objective Research the dose–response relationship between overall and certain types of exercise and cognitive function in older adults with Alzheimer's disease and dementia. Design Systemic and Bayesian Model-Based Network Meta-Analysis. Methods In our study, we analyzed data from randomized controlled trials investigating the effects of different exercises on cognitive outcomes in older adults with AD. We searched the Web of Science, PubMed, Cochrane Central Register of Controlled Trials, and Embase up to November 2023. Using the Cochrane Risk of Bias tool (Rob2) for quality assessment and R software with the MBNMA package for data analysis, we determined standard mean differences (SMDs) and 95% confidence intervals (95%CrI) to evaluate exercise's impact on cognitive function in AD. Results Twenty-seven studies with 2,242 AD patients revealed a nonlinear relationship between exercise and cognitive improvement in AD patients. We observed significant cognitive enhancements at an effective exercise dose of up to 1000 METs-min/week (SMDs: 0.535, SD: 0.269, 95% CrI: 0.023 to 1.092). The optimal dose was found to be 650 METs-min/week (SMDs: 0.691, SD: 0.169, 95% CrI: 0.373 to 1.039), with AE (Aerobic exercise) being particularly effective. For AE, the optimal cognitive enhancement dose was determined to be 660 METs-min/week (SMDs: 0.909, SD: 0.219, 95% CrI: 0.495 to 1.362). Conclusion Nonlinear dose–response relationship between exercise and cognitive improvement in Alzheimer’s disease, with the optimal AE dose identified at 660 METs-min/week for enhancing cognitive function in AD.